2022
DOI: 10.3390/v14030485
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter jejuni Developed the Resistance to Bacteriophage CP39 by Phase Variable Expression of 06875 Encoding the CGPTase

Abstract: Bacteriophage (phage) is regarded as an antimicrobial alternative for Campylobacter in food production. However, the development of phage resistance to the host is a main concern for the phage application. This study characterized the phage CP39 and investigated the phage resistance of CP39 in Campylobacter jejuni NCTC12662. We determined that phage CP39 belonged to the Myoviridae family by the WGS and phylogenetic analysis. Phage CP39 was confirmed as a capsular polysaccharide (CPS)-dependent phage by primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…For bacteriophage therapy, it is necessary to solve the development of bacteriophage resistance to the host. However, the mechanism of bacteriophage resistance is rarely reported, we lack detailed knowledge about their ecological and evolutionary interactions ( Kortright et al, 2019 ; Markwitz et al, 2021 ; North and Brown, 2021 ; Tang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…For bacteriophage therapy, it is necessary to solve the development of bacteriophage resistance to the host. However, the mechanism of bacteriophage resistance is rarely reported, we lack detailed knowledge about their ecological and evolutionary interactions ( Kortright et al, 2019 ; Markwitz et al, 2021 ; North and Brown, 2021 ; Tang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bacteriophages are “viruses that can infect and kill targeted bacterial cells” [ 166 ]. They have been extensively researched and used as antimicrobial agents worldwide for the treatment of several human diseases and recently as preventative and therapeutic agents to control Campylobacter colonization in poultry [ 167 , 168 , 169 , 170 , 171 , 172 ]. In a recent study, oral administration of two field bacteriophages to experimentally infected broiler chickens at 37 days of age significantly reduced Campylobacter counts by 2 log 10 CFU/g at 40 days of age [ 168 ].…”
Section: Pre-harvest Control Measures (On-farm Control)mentioning
confidence: 99%
“…However, phage cocktails must be carefully designed based on the types of phages being administered to achieve maximal benefits as phages exhibit different mechanisms of infection. For example, group 2 phages isolated from C. jejuni RM1221 typically use flagella as a route of entry, while group 3 phages isolated from C. jejuni NCTC12662 target bacterial capsular polysaccharide receptors [ 171 , 173 ]. In this context, Hammer et al [ 174 ] have demonstrated that administration of a group 3 phage CP14 alone reduced fecal counts by 1 log 10 , while when co-administered with CP81, which belongs to the same group, no further reduction in fecal Campylobacter count was observed.…”
Section: Pre-harvest Control Measures (On-farm Control)mentioning
confidence: 99%
“…The lack of homogenization of the species may be due to the existence of subpopulation-specific barriers to genetic exchange. A multitude of mechanisms exist that prevent entry of foreign DNA into the bacteria, such as variation of capsular polysaccharides or of flagellar structures ( 8 , 9 ). Two powerful barriers for genetic exchange after the DNA has entered the cell include clustered regularly interspaced palindromic repeat (CRISPR)-directed nucleases that can destroy DNA carrying a specifically recognized sequence ( 10 13 ) and restriction/modification systems ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%